Students Perceptions of The Implementation of Blinded Learning in a Large English Class - Fachri Ali (LP2M IAIN Pekalongan, 2017)
This study aims to investigate the students perceptions of the implementation of BL in a large English class and explare how BL enhances the students engagement in large english class. This study was designed as qualitative research. It employed an action research design of three cycles. The research finding reveal that (1) 75% of the respondents commented that implemantation of BL helped make the course work and activities interesting in their large class. Relating to language skills, 70% of the student also gave a positive perception on the implementation of BL model. It helped them enhance their language skills, particularly reading and writing. This result illustrates that the language skills can be also enhanced by incorporating technological pedagogy as a part of language intruction. (2) 75% of the research participants rated themselves as more engaged. The four items dealing with interaction during the course had medium effects: online course by using edmodo and face to face component in their large class enhancing each other (78%), likelihood to ask question (65%), quality of interaction with other students (77%), and icreased interaction with the lecturer (72%).